The 'other woman' in a mother and daughter relationship: The case of Mami Ji. (27th February 2017) - Creese, Angela; Blackledge, Adrian
ABSTRACT: This article describes the range of discursive strategies in the socializing messages of a mother and daughter interaction. The analysis draws on the work of Bakhtin (1981) and Tannen (2007) to interrogate the role of a physically absent but discursively present sister-in-law, 'Mami Ji', across three speech events. Following Tannen, we show how the characterisation of the sister-in-law, Mami Ji, has chronotopic value that connects mother and daughter in the present and makes links across family histories. Through the discursive strategies of repetition, dialogue, detail, and translanguaging, 'Mami Ji' becomes an iconic benchmark of how not to speak, how not to dress, and how not to behave. Drawing on material from a linguistic ethnography approach, we present three discourse analyses from a much larger international project that also looked at classroom interaction and break-time conversations. The article contributes to the under-researched topic of the representation of sisters-in-law in discourse, theorises the chronotope in everyday conversation, and demonstrates how mother and daughter solidarity is achieved through opposition to another female family member. (Chronotope, linguistic involvement strategies, translanguaging, socialisation, sister-in-laws, mothers and daughters)